Changes in knee flexion-extension performance and hamstring-to-quadriceps ratio during a fatiguing isokinetic protocol in male professional futsal players - Machado, C. L. F.; Nakamura, F. Y.; Fortes, R. P.; Trapaga, I. D.; Brusco, C. M.; Pinto, M. D.; Pinto, R. S. (International Journal of Performance Analysis in Sport, 2023)
Knee flexion (KF) and extension (KE) performance and hamstring-to-quadriceps (H:Q) ratio are used to estimate injury risk and readiness to return to sport. However, the traditional measures (i.e. non-fatigued state and by peak torque [PT]) may not reflect the thigh and knee injury conditions (i.e. high-speed actions and fatigue presence). We verified the effects of a high-speed isokinetic fatigue protocol (30 consecutive KF and KE concentric contractions at 300°/s) on KF and KE performance and H:Q ratios assessed through different parameters (i.e. PT, work, average and peak power) in male professional futsal players (n = 17). A significant (p < 0.01) time × muscle group interaction was verified. There were reductions (p < 0.01) in KF by PT (84.79 ± 15.05 to 50.29 ± 15.29 Nm), work (87.28 ± 14.46 to 39.00 ± 13.83 Nm), average power (227.81 ± 39.31 to 104.75 ± 31.24 W) and peak power (383.40 ± 59.90 to 191.39 ± 48.35 W). Similarly, KE performance decreased (p < 0.01) for all parameters (PT: 131.36 ± 16.05 to 81.61 ± 9.15 Nm; work: 148.83 ± 20.88 to 90.72 ± 11.89 Nm; average power: 148.83 ± 20.88 to 90.72 ± 11.89 W; peak power: 664.74 ± 85.32 to 398.38 ± 42.42 W). KF (-55.18 ± 13.91% to -40.94 ± 12.66%) showed a higher percentage decrease than KE (-40.46 ± 7.38% to -37.45 ± 6.61%). Finally, reductions (p < 0.01) in H:Q ratio by work, average and peak power but not by PT (p = 0.25) were verified. The tested methods can provide additional information about the athlete`s condition.